2008
DOI: 10.1513/pats.200707-092et
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Aspects of Chronic Obstructive Pulmonary Disease

Abstract: It is clear that being underweight is a poor prognostic sign in chronic obstructive pulmonary disease (COPD). It is also clear that undernutrition is at least in part associated with the severity of airflow obstruction. While both weight and body mass index are useful screening tools in the initial nutritional evaluation, fat-free mass (FFM) may be a better marker of undernutrition in patients with COPD. The causes of cachexia in patients with COPD are multifactorial and include decreased oral intake, the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 29 publications
1
43
0
10
Order By: Relevance
“…In COPD patients, both physical inactivity due to exercise intolerance [29] and systemic inflammation [3] may explain the prevalent loss of fat-free mass. In addition, the expansion of extracellular and intracellular water volumes, driven by hypoxaemia, may explain why malnutrition may occur despite normal weight [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COPD patients, both physical inactivity due to exercise intolerance [29] and systemic inflammation [3] may explain the prevalent loss of fat-free mass. In addition, the expansion of extracellular and intracellular water volumes, driven by hypoxaemia, may explain why malnutrition may occur despite normal weight [30].…”
Section: Discussionmentioning
confidence: 99%
“…Amongst these, malnutrition is very common and its prevalence increases along with the severity of the disease [3,4]. Malnutrition has been recognised as a risk factor for mortality [5].…”
Section: 037)mentioning
confidence: 99%
“…Impaired energy balance, due to elevated energy requirements, reduced dietary intake, or both, may lead to limb muscle atrophy (380,381). The energy balance may be compromised in COPD due to the complex interaction of a number of factors, including anorexia, elevated whole-body energy requirements, imbalance between muscle protein synthesis and breakdown, enhanced lipolysis, and an increase in pulmonary and systemic inflammatory mediators (382). Impairment in energy balance and protein balance may occur simultaneously, but these processes can also be dissociated, as reflected in the different COPD body composition phenotypes.…”
Section: Mechanisms Of Limb Muscle Dysfunction In Copdmentioning
confidence: 99%
“…10,13,27 It has been shown that, in these patients, weight loss and muscle wasting are associated with an increased risk of acute exacerbations, hospital admissions, and the need for mechanical ventilation. 10 It has been observed that muscle wasting and weight loss affects about 33% of patients with chronic respiratory disease.…”
Section: Nutritional Interventionmentioning
confidence: 99%